Micro-irrigation - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Irrigation is an essential practice in many agricultural production systems. It is also one of the oldest interventions to nature implemented by humankind, since its origins trace back to almost 6000 BC [1]. Currently, agriculture accounts for 70% of all freshwater withdrawals globally, with irrigation being the primary driver. As shown in Figure 1, irrigation is closely linked to an increase in crop yields. On average at the global level, yields achieved under irrigation are almost double relative to rainfed yields, with potential for even greater yield increase in arid areas. Since water is a scarce resource, particularly in arid and semi-arid regions, satisfying the increased demand for irrigation water in agriculture has become a pressing global challenge, exacerbated by climate and demographic change, which will require an increased supply of food for a growing human population [2]. The high demand for irrigation water to support food production is linked to several types of nature losses, the most important of which is the risk of water resources depletion [3] and the subsequent negative impacts on water-related biodiversity and ecosystem services. Figure 2 illustrates the consumption rate of renewable water resources, highlighting how arid and semi-arid regions frequently surpass the natural replenishment rate of their water resources. Furthermore, irrigation can cause soil degradation by inducing changes in soil structure and increasing the risk of erosion [4]. Flood irrigation, in particular, can contribute to soil erosion by physically moving the soil parts. In arid and semi-arid regions, high evaporation rates of irrigation water from the soil surface can cause problems of salinization over time. In regions where irrigated agriculture is prevalent, these environmental risks significantly increase with water overconsumption or inefficient water use.